CAMPUR TANGAN PIHAK KETIGA TERHADAP DOKUMEN PEMBAYARAN PERDAGANGAN INTERNASIONAL ( LETTER OF CREDIT ) DI INDONESIA - Totok Tumangkar (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
An import-export trading transaction is essentially a simple transaction that is nothing more than buying and selling goods between different buyers and sellers. In the transaction known as the form of payment with Letter of Credit (L / C), in the stage of development, originally L / C is based only mutual trust between buyer and seller or between importer and exporter. The seller only gets assurance that the payment will be made with Bank services. Thus, in the opening of the L / C, besides the Exporter and importer will be involved in third party Bank. Bank is a party that can give confidence and certainty to exporter that payment will be made by Bank in accordance with the requirements contained in the L / C. Against the L / C the legal provisions governing and enacting are the provisions set out in the Uniform Customs and Practice for Documentary. The third party's intervention especially the Bank is only against documents and not with goods.